Impact of two-electron dynamics and correlations on high-order-harmonic generation in He - Artemyev, Anton; Cederbaum, Lorenz S.; Demekhin, Philipp V. (Physical review, 2017)
The interaction of a helium atom with an intense, short, 800-nm, laser pulse is studied theoretically beyond the single-active-electron approximation. For this purpose, the time-dependent Schrödinger equation for a two-electron wave packet driven by a linearly polarized infrared pulse is solved by the time-dependent restricted-active-space configuration-interaction method in the dipole velocity gauge. By systematically extending the space of active configurations, we investigate the role of the collective two-electron dynamics in the strong-field ionization and high-order-harmonic generation processes. Our numerical results demonstrate that allowing both electrons in He to be dynamically active results in a considerable extension of the computed high-order-harmonic generation spectrum.